Decorating a Christmas tree in primary school - SIMBARTL, PETR; TANKOVÁ, HELENA (Journal of Education, Technology and Computer Science, 2017)
This contribution is dealing with usage options of various material types for a creation of Christmas decorations at the first level of primary school. It summarizes creation from natural materials, paper, a combination of different materials as well as modelling materials. All these types of materials were tested at primary school with children. We also show here results of chil-dren’s work, that they can create themselves. It comes to combining several parts during the classes, namely the promotion of the tradition of Christmas tree decorations, Christmas traditions linked to this and intersubject relations (elementary science and social studies). By creating products, we improve children´s fine motoring and with some products we support creativity.